2023
DOI: 10.1002/cb.2244
|View full text |Cite
|
Sign up to set email alerts
|

When consumers have difficulty understanding ads: How technical language lowers purchase intention

Jiayao Liu,
Xinyue Hong,
Zhixing Zheng
et al.

Abstract: Technical language refers to field‐specific professional terms that are unfamiliar to general consumers. Despite consumers' lack of familiarity with technical language, it is still used in advertisements for various products. Here, we find that technical language reduces consumers' willingness to purchase the advertised products because such language reduces their processing fluency (Study 1 and Study 2). We further show that (1) when consumers have relevant knowledge (Study 3) and (2) when the advertised prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…As one of the essential mechanisms in matching research, processing fluency significantly impacts subsequent behavioral decisions. The use of technical language in advertisements reduces consumers' willingness to buy because this language reduces their processing fluency, especially for the average consumer Liu et al (2023), However, Pan's 2020 study showed that the negative impact of technical language is attenuated when consumers have relevant knowledge or when the advertisement involves a typical technical product (Yating et al, 2020). Fu explored the external stimuli and internal psychological characteristics that influence the effectiveness of green advertisements, considering the interactions of message framing, environmental attitudes, and processing fluency.…”
Section: Mediation Of Processing Fluencymentioning
confidence: 99%
“…As one of the essential mechanisms in matching research, processing fluency significantly impacts subsequent behavioral decisions. The use of technical language in advertisements reduces consumers' willingness to buy because this language reduces their processing fluency, especially for the average consumer Liu et al (2023), However, Pan's 2020 study showed that the negative impact of technical language is attenuated when consumers have relevant knowledge or when the advertisement involves a typical technical product (Yating et al, 2020). Fu explored the external stimuli and internal psychological characteristics that influence the effectiveness of green advertisements, considering the interactions of message framing, environmental attitudes, and processing fluency.…”
Section: Mediation Of Processing Fluencymentioning
confidence: 99%